2006
DOI: 10.1186/1476-0711-5-5
|View full text |Cite
|
Sign up to set email alerts
|

Tabebuia avellanedae naphthoquinones: activity against methicillin-resistant staphylococcal strains, cytotoxic activity and in vivo dermal irritability analysis

Abstract: BackgroundMethicillin-resistant Staphylococcus aureus (MRSA) and coagulase-negative staphylococcus infections are a worldwide concern. Currently, these isolates have also shown resistance to vancomycin, the last therapy used in these cases. It has been observed that quinones and other related compounds exhibit antibacterial activity. This study evaluated the antibacterial activity, toxicity and in vivo dermal irritability of lapachol extracted from Tabebuia avellanedae and derivatives against methicillin-resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(17 citation statements)
references
References 20 publications
2
14
0
1
Order By: Relevance
“…Although C. dubliniensis colonies are dark green unlike light green colonies of C. albicans , this difference may be inadequate for primary identification and often lost after serial subculture. [2324] Hospenthal et al reported all C. dubliniensis strains ( n = 17) in their study had colonies identical to C. albicans on CAC. In this study, we isolated one C. dubliniensis, which had typical dark green colonies.…”
Section: Discussionmentioning
confidence: 95%
“…Although C. dubliniensis colonies are dark green unlike light green colonies of C. albicans , this difference may be inadequate for primary identification and often lost after serial subculture. [2324] Hospenthal et al reported all C. dubliniensis strains ( n = 17) in their study had colonies identical to C. albicans on CAC. In this study, we isolated one C. dubliniensis, which had typical dark green colonies.…”
Section: Discussionmentioning
confidence: 95%
“…It was found that the (-)-5-hydroxy-2-(1'-hydoxyethyl) naphtho [2,3-b]furan-4,9-dione (3) and its positional isomer (-)-8-hydroxy-2-(1'-hydoxyethyl) naphtho [2,3-b]furan-4,9-dione (4) had a strong activity against Staphylococcus aureus and Bacillus subtilis, with MICs varying between 0.78 and 6.25 µg/mL (0.78 and 6.25 mg/L) (Yamashita et al 2009); these naphthoquinones are found in the inner bark of Tabebuia avellanedae (Wagner et al 1989). Other naphthoquinone derivatives obtained from the Tabebuia avellanedae-isolated lapachol (5), such as β-lapachone (6) and (±) 3-hydroxy-β-Nlapachone (7), displayed a considerable inhibitory activity against Staphylococcus aureus growth, with MICs of 8 µg/mL (8 mg/L) for both compounds; however, no bactericidal activity was observed (Minimum Bactericidal Concentration, MBC≥512 µg/mL (512 mg/L) (Pereira et al 2006). Lapachol, which is a biologically active naphthoquinone showed activity against several agents such as bacteria, fungus, viruses and parasites and has therefore been used as a target for the synthesis of naphthoquinone derivatives with potent antimicrobial activity (Hussain et al 2007).…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…The expression of NQO1 in solid cancers is higher than in normal tissues (Belinsky and Jaiswal., 1993), including in carcinoma of the liver (Schlager and Powis, 1990), colon (Smitskamp-Wilms et al, 1995), breast (Schlager and Powis, 1990;Smitskamp-Wilms et al, 1995), brain (Berger et al, 1985), and lung (Schlager and Powis, 1990). In addition, NQO1 has been shown to be an important factor in β-lapachone-induced cell death in many kinds of cancer cells (Pink et al, 2000;Reinicke et al, 2005), including breast cancer (Tagliarino et al, 2003), glioma (Park et al, 2011), and prostate cancer (Pink et al, 2000). In this context, other methods have been examined to increase NQO1 expression or activity in cancer cells (Terai et al, 2009;Tan et al, 2012;Satsu et al, 2012) in order to increase the clinical efficacy of β-lapachone.…”
Section: Mnpces (N)mentioning
confidence: 99%
“…The anticancer activity of β-lapachone may involve its catalysis by NAD(P) H:quinone oxidoreductase (NQO1, DT-diaphorase), which used NAD(P)H or NADH as an electron source to yield the two-electron reduction of β-lapachone (Pardee et al, 2002;Reinicke et al, 2005). In the presence of NQO1, β-lapachone underwent reduction to an unstable hydroquinone, resulting in the generation of ROS, including superoxides (Pink et al, 2000;De Witte et al, 2004;Choi et al, 2007). In turn, these reactive oxygen species oxidized thiol groups of the mitochondrial potential transition pore complex, leading to increased inner membrane permeability, reduced membrane depolarization, release of cytochrome c, and cell death (Lemasters et al, 1998;Smaili et al, 2000).…”
Section: Mnpces (N)mentioning
confidence: 99%